Hubungan Supervisi Kepala Ruangan dengan Kinerja Perawat dalam Pendokumentasian Asuhan Keperawatan di Ruangan IGD RSUD Kota Kotamobagu - Norman Alfiat Talibo; Irma M Yahya (Universitas Muhammadiyah Manado, 2024)
The head of the ward has a crucial role in supervising health services, especially in supervising nurses regarding documentation of nursing care. This supervision functions to improve nurse performance. This study aims to determine the relationship between the supervision of the head of the room and the performance of nurses in documenting nursing care in the emergency room at Kotamobagu City Hospital.The method used is correlational analytics with a sample of 33 respondents taken by total sampling. Data collection was carried out through questionnaires and observation sheets, and analyzed using the Chi-Square Test with a significance level of 0.05.The research results showed that most of the supervision of room heads was in the good category (72.7%), but most of the documentation of nursing care was still incomplete (69.7%). The Chi-Square test produced a value of p = 0.020, which is smaller than 0.05, indicating a significant relationship between the supervision of the head of the room and the performance of nurses in documentation. In conclusion, there is a positive relationship between the supervision of the head of the room and the documentation performance of nurses. It is hoped that the quality of documentation can be improved through seminars or workshops, as well as supervision and leadership training, so that room heads can become role models for nurses in carrying out their duties.